Dampak Psikologis Remaja Akibat Orang Tua Tidak Dapat Meluangkan Waktu Akibat Bekerja - Suci Rahma Dini; Taufik Surya Romadhon; Yusup Kholid Akbar; M Habib Fajar Gianisam (Yayasan Darussalam Bengkulu, 2025)
This research is motivated by several adolescents who cannot plan responsible social behavior and they do not understand how they should behave in society, one of which is caused by parents who are busy working, this greatly affects development during adolescence, especially for adolescent psychology, it is known that there are several adolescents whose behavior is not in accordance with adolescents in general, their behavior tends to be negative. There are two problems studied in this thesis, namely (1) How is the Psychological Impact of adolescents due to parents being busy working, (2) What efforts are made by parents to be able to provide sufficient attention to adolescents when they are busy working. The purpose of this study was to determine the psychological impact on adolescents due to parents being busy working and what efforts parents make to be able to provide sufficient attention to adolescents while busy working. The research method used is descriptive qualitative. This type of research is field research. The determination of research informants used a purposive sampling technique. The informants in this study were adolescents whose parents were busy working and parents. The total number of informants was 14 people. The results of the study revealed that (1) The psychological impact on adolescents due to parents being busy working is: feeling ashamed of friends, feeling anxious because parents are often not at home, and experiencing obstacles in learning such as difficulty concentrating and being lazy to do schoolwork. (2) Efforts made by parents to provide sufficient attention to adolescents while busy working are: 1. Entrusting children to neighbors or close family so that parents can find out about their child's behavior, 2. guiding children in learning patiently and following the child's learning method and meeting the needs required by children in learning activities, 3. Providing advice by calling or sending short messages